New Metrics for New Values of Police Management. Value Criteria and Measurement of Spanish Local Police Action in Relational Governance Scenarios - Carmona Pérez, Carlos; Natera Peral, Antonio (Revista del CLAD Reforma y Democracia, 2021)
The deep technical-competence transformation in which Spanish local police forces are immersed converges with a change in their management model which is oriented towards the emerging paradigm of governance. In this context, the renewal of classic police metrics acquires special relevance. The main goal of the article is to design an original and referential catalog of value criteria and key indicators for the measurement of municipal police action associated with the relational-governance oriented police model. To this end, the discussion of conceptual, methodological aspects and difficulties of the evaluation and measurement of police agency is presented. A basic table of value criteria related to different police models is also identify, with special reference to the relational police model. Finally, the integrative design of indicators according to the previously identified value criteria and main scenarios of police action at the municipal level is addressed.